2023
DOI: 10.1186/s13756-023-01218-y
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of tooth brushing on oral bacteriota and health care-associated infections among ventilated COVID-19 patients: an intervention study

Abstract: Background Up to 48% of ventilated coronavirus disease 2019 (COVID-19) patients develop ventilator-associated pneumonia (VAP) during hospitalization in an ICU. Dysbiotic oral microbiota can colonize the lower respiratory tract and lead to VAP. It is recommended to introduce oral care strategies in the ICU to prevent VAP. In this study, we observed the impact of an oral hygienic protocol with tooth brushing on cultivable oral bacteriota, the incidence of HAI and patient safety among mechanically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 47 publications
0
7
0
5
Order By: Relevance
“…colonization and qualitative shifts towards higher identification rate of non-albicans Candida species [ 38 ]. Previous studies showed significant alarming dysbiosis of oral bacteriota in such populations [ 18 ], with high rates of healthcare-acquired infections of Acinetobacter baumannii, Enterococcus faecalis, Escherichia coli, and Klebsiella pneumoniae etiology [ 13 ]. Poor oral health status, high frequency of oral colonization by potentially pathogenic bacteria and early postintubation dysbiosis may also play a significant role in the development of candidiasis [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…colonization and qualitative shifts towards higher identification rate of non-albicans Candida species [ 38 ]. Previous studies showed significant alarming dysbiosis of oral bacteriota in such populations [ 18 ], with high rates of healthcare-acquired infections of Acinetobacter baumannii, Enterococcus faecalis, Escherichia coli, and Klebsiella pneumoniae etiology [ 13 ]. Poor oral health status, high frequency of oral colonization by potentially pathogenic bacteria and early postintubation dysbiosis may also play a significant role in the development of candidiasis [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the observation, patients received two types of oral care—the standard procedure that included cleaning, moisturizing of oral cavity and suction of excess fluid or the extended procedure with additional tooth brushing. The detailed description of the intervention and its effects on oral bacteriobiota has been published elsewhere [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bei sehr schlechtem Dentalzustand (massiver Zahnstein, Entzündungen, tiefe Zahntaschen usw.) ist eine zahnärztliche Konsultation zu erwägen[9,10]. Die Zahn-und Mundpflege sollte mindestens 2-mal täglich durchgeführt werden.…”
unclassified